CRYSTAL CHEMISTRY OF CR-SPINEL FROM THE IMANDRA LAYERED PLUTON, KOLA PENINSULA - Zaitseva T.S.; Goncharov G.N.; Gittsovich V.N.; Semenov V.G. (My University, 2001)
Cr-spinel from the Imandra layered pluton was studied by a variety of methods including mineralogical and petrographic investigations, microprobe, infrared (IR) spectroscopy, XRD, and Mössbauer spectroscopy on 57Fe nuclei. The Imandra Cr-spinel is a multicomponent (Fe2+, Mg)(Cr, Al, Fe3+)2O4 solid solution, which underwent exsolution during cooling after being crystallized to form two major cluster groups composed of chromite and spinel; the domain size was not larger than 6 μm. The concordant variation of chemical compositions in both cluster groups was governed by the equilibrium redistribution of chemical elements according to the occupancy of energetically advantageous cation sites.